2018
DOI: 10.1111/are.13936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density on reared Siberian sturgeon (Acipenser baerii) larval growth, muscle development and fatty acids composition in a recirculating aquaculture system

Abstract: This study evaluated the effects of rearing density on muscle growth and development in Siberian sturgeon (Acipenser baerii) larvae. Three different stocking densities were tested: low (LD, 30 larvae/l), mid (MD, 80 larvae/l) and high (HD, 150 larvae/l) in a recirculating aquaculture system. Larvae were sampled at hatching (T0), schooling (T1) and complete yolk-sac absorption (T2) stage and were weighed and processed for muscle tissue histometrical analyses and for qualitative morphological study analyses; fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…As for growth-related genes expression, overall, it seems that high densities (particularly MD) lead to a higher expression of both igfs and myog at T2 when compared to T1. Reference [62] observed that Siberian sturgeon larvae subjected to LD and MD presented higher muscle fibers proliferation at the end of the trial, as well as a higher area of polygonal fast fibers, when compared to HD. These results are consistent with what was obtained in the present study, taking into account that IGFs in fish stimulate myogenic cells proliferation and differentiation [63,64] and that the gene myog is a marker of myogenic cell recruitment for stratified hyperplasia in teleosts [65].…”
Section: Discussionmentioning
confidence: 99%
“…As for growth-related genes expression, overall, it seems that high densities (particularly MD) lead to a higher expression of both igfs and myog at T2 when compared to T1. Reference [62] observed that Siberian sturgeon larvae subjected to LD and MD presented higher muscle fibers proliferation at the end of the trial, as well as a higher area of polygonal fast fibers, when compared to HD. These results are consistent with what was obtained in the present study, taking into account that IGFs in fish stimulate myogenic cells proliferation and differentiation [63,64] and that the gene myog is a marker of myogenic cell recruitment for stratified hyperplasia in teleosts [65].…”
Section: Discussionmentioning
confidence: 99%
“…Farming of sturgeons is economically and ecologically important due to their high nutrition values (meat and caviar) and prevents their mass extinctions from natural ecosystems (Chebanov & Galich, 2018; Geraylou et al, 2013). Siberian sturgeon ( Acipenser baerii , Brandt, 1869) has some potential characteristics such as fast growth, high compatibility with artificial diets, tolerance to unfavourable environmental conditions and a short period of sexual maturity makes it an ideal species compared to other sturgeons (Acipenseridae) for aquaculture operations (Aidos et al, 2019; Fopp‐Bayat et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in stocking density in the present study did not have effect on growth of sterlet larvae. The productivity of aquaculture systems can be increased by increasing the number of cultured fish per volume unit (Aidos et al, 2018;Barros et al, 2019;Montero et al, 1999). On the other hand, this may impact water quality and welfare status visible in culture performance, physiological status, and the behavior of farmed fish.…”
Section: Discussionmentioning
confidence: 99%
“…For farms and hatcheries, it is important to keep up with the increasing demands for both meat production and restocking purposes which can be achieved by having large quantities of juveniles. The efficiency of intensive aquaculture systems might be optimized by increasing the stocking density (Aidos et al, 2018; Barros et al, 2019). High rearing density may have a disadvantageous impact on fish culture proven to impair physiological status in various teleosts as well as the welfare and behaviour of reared fish (Barros et al, 2019; Bolasina et al, 2006; Lupatsh et al, 2010; Montero et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation